Evaluation Model for WWTP Feasibility Palm Industry in West Sumatera - Dewata, Indang (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This research is motivated by the collapse of the WWTP pool PT. Binapratama Sakatojaya South Solok, namely pond Anaerobic pond 2 which occurs due to very high rainfall and lasts a long time, so that the embankment cannot hold the volume and discharge of wastewater at that time. The company is required to repair the broken embankment and conduct a feasibility study of the embankment conducted by the independent PPKLH UNP team. The purpose of this study is to analyze and provide recommendations on the feasibility of WWTP PT. Binapratama Sakatojaya South Solok. Primary data collection is done by surveying the location of the study, water sampling, testing the quality of wastewater, ground water and surface water and soil sampling. Secondary data used include maps (administrative maps, maps of plantation locations, and maps of PT. Binapratama Sakatojaya Selatan Solok and land applications). The research findings reveal: (1) There was no water pollution from the analyzed water samples either wastewater, ground water and surface water which were sampled on June 20, 2019. (2) Making wooden pile on the inside of the embankment that serves to hold the soil or restrain the entry of water into the dug hole. (3) The embankment used has met the strong requirements for shear and rolling both in conditions without earthquake loads and with earthquake loads.